Synthesis of acetic acid via methanol hydrocarboxylation with CO2 and H2 - Qingli Qian (Nature Portfolio, 2016)
Industrial routes to acetic acid use carbon monoxide for the carbonylation of methanol. Here, the authors report a hydrocarboxylation method that instead uses carbon dioxide and hydrogen for the conversion of methanol into acetic acid.